A study on the relationship between gross domestic product and macroeconomic variables in Malaysia / Suriani Ruzalle (Faculty of Business and Management, 2008)
This project paper is to identify the relationship between Gross Domestic Product and macroeconomic variables in Malaysia. These four independent variables are the main function that contributes in the economic growth. The dependent variable is Gross Domestic Product (GDP) and the independent variables are export, import, Total employment and total investment. The study focuses on the annual data collected from 1975 until 2005. This research used the Statistical Package for Social Science (SPSS) by using the method of Simple Linear Regression Analysis to find out the relationship between dependent variable and independent variables. From the findings, it is concluded that GDP has a positive relationship with export, import, total investment, and total employment. Based on the T-statistic values the export, import, and total employment have significant relationships with the dependent variable, while only the total investment does not have a significant relationship with the GDP in Malaysia.